Determination and Distribution Map for Radionuclides in Soil Samples from Different Location by Gamma Spectrometry Using Software Analysis - H. Mansour; L. A. Najam; S. A. Abd El-Azeem (PPIKSN-BATAN, 2022)
The fundamental goal of the current study is to determine the mean activity concentrations of natural and artificial radionuclides of 226Ra, 232Th, 40K, and 137Cs using gamma spectrometry for three locations, in Egypt, Saudi Arabia, and Iraq, which are significant and vital countries in the Middle East. The mean absorbed dose rate equals 22.35, 28.96, and 43.34 nGy h-1 for Egypt, Saudi Arabia, and Iraq. The results are consistent with international reports. The dose contribution percentages for investigated locations are 24 %, 30 %, and 46 % for Egypt, Saudi Arabia, and Iraq, respectively. The obtained results were clarified by statistical measurements using one-way ANOVA test to determine the distribution and differences between the averages of the three groups under study, as they may be influenced by geological variations and human intervention. It was found that the Iraq samples followed a symmetrical, standard normal distribution, while samples from Egypt and Saudi Arabia did not. Statistically significant differences were found between the data from the three countries.